Analisis Forecasting Profitabilitas Bank Muamalat dengan Metode Analisis Tren Terbaik Periode Tahun 2008 – 2024 - M Saskia Muslihah; Moh Mukhsin; Nani Suhartini (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2026)
Abstract: This study aims to analyze and forecast the profitability of Bank Muamalat Indonesia for the 2008–2024 period using Return on Assets (ROA) and Return on Equity (ROE), addressing the critical issue of a persistent long-term profitability decline in Indonesia’s pioneering Islamic bank. Building on existing forecasting literature, this quantitative time-series research compares three trend models; linear, quadratic, and exponential through SPSS 23.0’s Curve Estimation to identify the best-fit model. The results show that the exponential trend model is the most accurate for both ROA and ROE, with Adjusted R² values of 0.814 and 0.780, respectively. Based on this model, five-year projections (2025–2029) indicate a continued downward trend, with profitability approaching critically low levels. These findings serve as an early warning signal and highlight the urgent need for strategic interventions to reverse Bank Muamalat’s structural profitability decline, offering crucial insights for management, investors, and regulators Keyword: Forecasting, Profitability, ROA, ROE, Trend Analysis, Bank Muamalat, Islamic Bank